(untitled) (Journal of Medical Sciences, 2021)
Human cryptosporidiosis is a major cause of diarrhea in developing countries and generally causes watery diarrhea in immunocompetent patients or chronic severe diarrhea in immunocompromised individuals. The present study was undertaken to investigate the prevalence of Cryptosporidium spp. infection among pediatric patients with diarrhea, attending Sebha Medical Center for their health problems. One hundred children were included in the study, in the age group from 1 to 10 years old, selected from Outpatient clinic Sebha Medical Center, Sebha. All the stool samples were screened for presence of Cryptosporidium oocysts, using Modified Ziehl-Neelsen staining techniques. Ten children (10%) in the study group were found positive for Cryptosporidium infection using Modified Ziehl Neelsen staining method. No, significant differences (x2=6.678, p = 0.410) were found between boys (7.69%) and girls (12.50%) for the detection Cryptosporidium oocysts. Significant difference (x2=18.264, p=0.021) was found between the different age groups of children for the diagnosis of cryptosporidiosis. Modified Ziehl-Neelsen staining technique was proved to be simple and useful for routine detection and identification of Cryptosporidium spp. oocysts in fresh fecal samples.